PENGGUNAAN METODE BERMAIN PERAN DALAM MENINGKATKAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI KB LESTARI DESA SUNGAI RUSA KECAMATAN SELAKAU TAHUN PELAJARAN 2022-2023 - Resa Nabila (Samawa (Sakinah, Mawaddah Warahmah), 2023)
This article aims to describe and find out about: 1) Describe planning for the development of social emotional abilities in early childhood through role playing methods; 2) Describe how the implementation of role playing methods can develop children's social and emotional development; 3) Describe the evaluation of the development of early childhood social emotional abilities. This research uses a qualitative method with a phenomenological approach. The results of this research show that: 1) Teachers in creating an environmental system that allows the learning process to occur is a necessity with the aim that learning objectives can be achieved optimally, therefore teachers are required to prepare daily learning implementation plans (RPPH). 2) The teacher creates a script for the storyline that will be played; The teacher gathers children to be given directions and rules for role playing; The teacher has prepared the tools that students will use to play; The teacher explains the tools that students will use to play; The teacher distributes tasks to students according to the roles they will play, so that they do not fight when playing roles; The teacher accompanies students in role playing. 3) Formative evaluation is intended to monitor student learning progress during the teaching and learning process and to identify weaknesses that require improvement so that teaching and learning outcomes become better.